Attitude of Healthcare Professionals towards People with Disabilities : an Exploratory Study - Farhana Fakhira Ismail (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2018)
Attitude of healthcare professionals gives big influence towards self-esteem of people with disabilities (PWD). The greatest challenges faced by PWD were not being treated with respect, not equipped with suitable equipment, and denied health services. This study aimed to identify general attitude of healthcare professionals towards PWD and to explore this attitudes from the perspective of PWD. A mixed method approach was conducted involving 350 healthcare professionals from Hospital Tengku Ampuan Afzan (HTAA) and 10 physically disabled people who used or still receiving treatment in HTAA in a cross-sectional survey and face-to-face in-depth interviews, respectively. A Scale of Attitudes toward Disabled Persons (SADP) was distributed to respondents and data were analyzed using IBM SPSS Statistics version 20. On the other hand, data from face-to-face in-depth interviews were analyzed using thematic analysis.The quantitative findings revealed physicians have the most favorable attitude followed by optometrists. Meanwhile the least favorable attitude were shown by medical assistant followed by nurses. From the perception of PWD, majority of the participants were satisfied with positive attitude shown by healthcare professionals though negative attitude was claimed to exist in some situations. With respect to gender, from quantitative findings, males were significantly having more favorable attitudes compared to female (p=0.002). Meanwhile, from in-depth interviews, the participants mentioned that there was no difference in attitude shown with regard to gender. Besides, in terms of age and working experience, quantitative findings revealed weak negative correlation between age and working experience in relation with attitude towards PWD. However, from the qualitative findings, the participants mentioned about older healthcare professionals are advance in terms of their knowledge and experience. Six themes were emerged from saturated data namely: Being as PWD, sensitivity and care, challenges encountered, support towards PWD, health professionals' attitude towards PWD, hospital's facilities and services provided for PWD, and implications towards PWD. Majority of the participants expressed to feel demotivated and having low self-esteem after having their impairment. Support from close family members and friends are really significant to boost their self-esteem and motivation. Problems encountered in healthcare setting should be overcome in order to ensure PWD are able to adherence to appointment and rehabilitation sessions.